BILATERAL TRANSVERSUS ABDOMINIS PLANE (TAP) BLOCK FOR TREATMENT OF CHRONIC ABDOMINAL WALL PAIN: A CASE REPORT - Toleska, Marija; Dimitrovski, Aleksandar; Kuzmanovska, Biljana; Kartalov, Andrijan; Kiprijanovska, Biljana; Toleska Dimitrovska, Natasha (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2022)
Transversus abdominis plane (TAP) block is a regional anesthesia technique where the local anesthetic is injected into the interfascial plane between the internal oblique and transversus abdominis muscle. This block is mainly used for treatment of acute pain following abdominal surgery. Persistent postsurgical pain (PPSP) or chronic postsurgical pain (CPSP) is pain that persists at least three months after surgery, which was not present before surgery, or which had different characteristics or increased intensity from preoperative pain. It is localized near the surgical site or a referred area, and other possible causes for the pain had been excluded (cancer recurrence or infection). This pain can lead to functional limitation and psychological trauma in patients. By presenting our case report we would like to describe the effect of TAP block on CPSP in a female patient who had previously undergone many abdominal surgeries.
Keywords: TAP block; chronic pain; abdominal wall